Soil Characteristics and Management of Ultisols Derived from Claystones of Sumatra - Pratamaningsih, Mira Media; Hati, Diah Puspita; Erwinda, Erwinda; Muslim, Rufaidah Qonita; Hikmat, Muhammad; Purwanto, Setiyo (UNIVERSITY OF LAMPUNG, 2024)
Ultisols are one of the soil types that develop from claystone parent materials and are widely distributed in Indonesia, making them suitable for agricultural land use. Naturally, Ultisols have low soil fertility, such as acidic soil reactions and low base content;Â without proper management, they can lead to suboptimal agricultural yields. Therefore, this study aims to determine the physical, chemical, and mineralogical characteristics of Ultisols to formulate appropriate land management practices. Soil samples were collected from Ultisols with claystone parent materials from various regions in Sumatra, Indonesia. Soil profile creation was conducted to observe soil morphology in the field, followed by physical, chemical, and mineralogical analysis in the laboratory. The results showed that the Ultisols studied have a deep solum (90-120 cm), clay texture, and sticky and plastic consistencies. These soils generally have an acidic reaction, low organic C content, low potential P and K contents, low cation exchange capacity, low base saturation, and high Al saturation. The contents of easily weathered minerals, such as orthoclase, biotite, augite, hypersthene, tourmaline, and andalusite, which are essential nutrient reserves, are also generally low. Thus, the Ultisols studied are classified as low fertility soils, requiring specific management practices such as adding lime, organic materials, and soil amendments in a balanced and appropriate manner to achieve optimal yields.